Coexistence of mutations in keratin 10 (KRT10) and the mitochondrial genome in a patient with ichthyosis with confetti and Leber's hereditary optic neuropathy. Issue 11 (25th September 2017) - Kalinska‐Bienias, Agnieszka; Pollak, Agnieszka; Kowalewski, Cezary; Lechowicz, Urszula; Stawinski, Piotr; Gergont, Aleksandra; Kosinska, Joanna; Pronicka, Ewa; Kowalski, Pawel; Wozniak, Katarzyna; Ploski, Rafal
Abstract : Ichthyosis with confetti (IWC) is a severe congenital genodermatosis characterized by ichthyosiform erythroderma since birth and confetti‐like spots of normal skin appearing in childhood as a results of revertant mosaicism. This disorder is caused by mutations in KRT10 or KRT1 g enes. We report a 16‐year‐old boy who presented ichthyosiform erythroderma with severe desquamation since birth and gradually worsening psycho‐neurological symptoms (mental retardation, ataxia, dystonia, hypoacusis). The patient conspicuously lacked typical confetti‐like spots at the age of 16. The molecular diagnostics by the whole exome sequencing showed a novel de novo (c.1374‐2A>C) mutation in the KRT10 gene responsible for the development of IWC ( KRT10 defect was confirmed by immunofluorescent study). Concurrently, the m.14484T>C mutation in mitochondrial MTND6 gene (characteristic for Leber's hereditary optic neuropathy or LHON) was detected in patient, his mother and brother. LHON causes frequent inherited blindness typically appearing during young adult life whose expression can be triggered by additional factors such as smoking or alcohol exposure. We speculate the effects of KRT10 and LHON mutations influence each other—skin inflammatory reaction due to severe ichthyosis might trigger the development of psychoneurological abnormalities whereas the mitochondrial mutation may reduce revertant mosaicism phenomenon resulting in the lack of confetti‐like spots characteristic for IWC. However, based on a single case we should be cautious about attributing phenotypes to digenic mechanisms without functional data.